Psychophysical evidence for an internal model of gravity in the visual and vestibular estimates of vertical motion duration - Sergio Delle Monache; Barbara La Scaleia; Anna Finazzi Agrò; Francesco Lacquaniti; Myrka Zago (Scientific Reports)
Abstract The motion of objects and ourselves along the vertical is affected by gravitational acceleration. However, the visual system is poorly sensitive to accelerations, and the otolith organs do not disassociate gravitational and inertial accelerations. Here, we tested the hypothesis that the brain estimates the duration of vertical visual motion and self-motion by means of an internal model of gravity predicting that downward motions are accelerated and upward motions are decelerated by gravity. In visual sessions, a target moved up or down while participants remained stationary. In vestibular sessions, participants were moved up or down in the absence of a visual target. In visual-vestibular sessions, participants were moved up or down while the visual target remained fixed in space. In all sessions, we verified that participants looked straight-ahead. We found that downward motions of either the visual target or the participant were systematically perceived as lasting less than upward motions of the same duration, and vice-versa for the opposite direction of motion, consistent with the predictions of the internal model of gravity. In visual-vestibular sessions, there was no significant difference in the average estimates of duration of downward and upward motion of the participant. However, there was large inter-subject variability of these estimates.